USE OF A DISTRIBUTED PROCESSING PLATFORM FOR PLAGIARISM POTENTIAL DETECTION WITH PROBABILITY INDICATORS OF CERTAIN IN HOMEWORKS SUBMITTED TO A SYSTEM OF COURSE MANAGEMENT. - Lavayen, D.; Cruz, E. (Nexo Revista Científica, 2017)
This paper presents the analysis, design, implementation and testing of a module for potential plagiarism detection of homework sent to a Course Management System, using the distributed processing platform Hadoop. This paper analyze the plagiarism problem that happened in homework done digitally by students and it are receipted by the Course Management Systems. Also, the paper shows a conceptual analysis for understanding how the necessity of comparing two sequences is present in other branches of science and how the solution has been proposed with the use of technological tools. Likewise, the document details how the problems were faced by dividing the process in two parts: the pre-processing of documents to generate plain text files and the implementation of the Smith-Waterman algorithm with the PhD. Robert W. Irving’s improvements. Finally, the paper shows a summary of testing results done over the distributed processing platform.